2020
DOI: 10.21203/rs.3.rs-110888/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perception to COVID-19 epidemic and acceptance of vaccination among healthcare workers in Beijing: a survey before the completion of COVID-19 vaccine phase III clinical trials

Abstract: Background: Covid-19 vaccine research and development is progressing and expected to be put into use in a predictable time, we aimed to learn the awareness and acceptance of the new vaccine by healthcare workers (HCWs) in Beijing, China. Methods: A cross-sectional survey was conducted to investigate HCWs including doctors, nurses and technicians from sixty hospitals in Beijing to obtain the perception of COVID-19 epidemic and the attitudes towards vaccination before before the completion of vaccine phase III c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…where 68.6% of the health-care workers were willing to get the COVID-19 vaccine [ 11 ]. Similar results were found in studies done in Romania in which 69% agreed with the COVID-19 vaccine [ 12 ] and Beijing where 67.1% reported that they would get vaccinated [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…where 68.6% of the health-care workers were willing to get the COVID-19 vaccine [ 11 ]. Similar results were found in studies done in Romania in which 69% agreed with the COVID-19 vaccine [ 12 ] and Beijing where 67.1% reported that they would get vaccinated [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“… 36 Kanyike et al 71 2021 600 Medical Students CS Uganda 37.3% Gender (female), marital status (single), perceived risk of getting COVID-19 in the future, receiving any vaccine in the past 5 years, and COVID-19 vaccine hesitancy. 37 Luodan et al 44 2020 8040 HCWs CS China 67.1% Perception of disease severity, self-infection risk and disease can be prevented by vaccine. 38 Machida et al 61 2021 2956 Adults (20 to 79 years) CS Japan 62.1% Gender, age, income level, perceived effectiveness of the COVID-19 vaccine, and willingness to protect others by getting oneself vaccinated.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the study reported that factors such as perceived risk of COVID-19, 30 , 31 , 34 , 44 , 47 , 50 , 51 , 53 , 58 , 59 , 68–71 trust in healthcare system, 46 , 51 health insurance, 31 , 48 norms, 31 , 65 attitude towards a vaccine, 31 , 55 , 58 perceived benefit of vaccine, 31 , 40 , 46 , 65 , 70 perceived vaccine barriers, 31 , 40 , 70 self-efficacy, 31 up-to-date on vaccinations, 32 being tested for COVID-19 in the past, 32 , 72 responsibility, 39 perceived efficacy of the COVID-19 vaccination, 41 , 47 use of social media for COVID-19 vaccine-related information, 41 recommended for vaccination, 34 political leaning, 34 perceived severity of COVID-19, 34 , 44 , 46 , 70 , 74 perceived effectiveness of a COVID-19 vaccine, 34 , 43 , 59 , 61 belief that vaccination makes them feel less worried about COVID-19, 59 believing in mandatory COVID-19 vaccination, 50 perceived potential vaccine harms, 34 , 42 , 53 , 58 presence of chronic disease, 45 , 48 , 60 previously received an influenza vaccine, 43 , 45 , 47 <...>…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations